2015
DOI: 10.1155/2015/312309
|View full text |Cite
|
Sign up to set email alerts
|

Sharp-Hook Acupuncture (Feng Gou Zhen) for Patients with Periarthritis of Shoulder: A Randomized Controlled Trial

Abstract: The Feng Gou Zhen (sharp-hook acupuncture) as a traditional form of ancient acupuncture is said to be particularly effective for managing periarthritis of shoulder. We conducted this randomized controlled trial to evaluate the effectiveness of Feng Gou Zhen as an add-on compared to conventional analgesics for patients with PAS. 132 patients were randomly assigned in a 1 : 1 ratio to either a acupuncture group receiving sharp-hook acupuncture plus acupoint injection with conventional analgesics or a control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Thus, the treatment of PAS is of great significance to increase people's life quality and advance public health. [16] However, conventional treatment of modern medicine that are associated with adverse events and side effect, cannot withdraw the symptoms and harmfulness of PAS completely. Therefore, it is necessary to search for alternative therapy with higher effective rate and less side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the treatment of PAS is of great significance to increase people's life quality and advance public health. [16] However, conventional treatment of modern medicine that are associated with adverse events and side effect, cannot withdraw the symptoms and harmfulness of PAS completely. Therefore, it is necessary to search for alternative therapy with higher effective rate and less side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these included studies reported that acupuncture is effective in relieving shoulder pain, 43,44 whereas others did not mention whether it is effective or ineffective in treating shoulder pain 26 or whether it is ineffective in treating shoulder pain; 45 Different acupuncture methods or tools have been used in studies on acupuncture to treat shoulder pain, such as bee venom acupuncture, 46 auricular acupuncture, 47 fire needles, 48,49 small needle-knife, 41 thread-embedding acupuncture, 50 warm-needle moxibustion and heat-sensitive moxibustion, 6 electroacupuncture, 51 and sharp-hook acupuncture. 52 Some studies are related to summarizing the common acupoints rules of acupuncture treating and moxibustion in shoulder pain, such as Tiaokou; 53 Chengshan acupoint; 54 Baihui acupoint; 55 Ashi points stimulation; 56 Zhongfu, Tianfu, Xiabai, Binao, Naohui, Jianliao, and Xiaoluo points; 57 distal-needling acupuncture; 58 and acupuncture on the opposite side of the pain to treat long-term shoulder pain. 59 "Dry needling", "trigger point", "injection", and "corticosteroid injection" are included in the top 10 most influential keywords (Table 7).…”
Section: Current Research Hotspots and Frontiersmentioning
confidence: 99%
“…However, there are fundamental differences in the pathogenesis between traumatic and nontraumatic shoulder pain, and most existing reviews did not distinguish between the two causes of shoulder pain in participants, potentially leading to bias in the conclusions. In recent decades, research on acupuncture for shoulder pain has continued, with new methods of acupuncture being developed and new evidence being produced that acupuncture is superior to many other treatments in relieving shoulder pain (33)(34)(35)(36)(37)(38)(39)(40). Thus, it is necessary to revisit the overall comparison between acupuncture and other interventions for common atraumatic shoulder pain.…”
Section: Introductionmentioning
confidence: 99%